Implementation Of Corporate Social Responsibility In Indonesia In The Perspective Of Legal Theory - Amanda Khairunisa Bunga (International Asia Of Law and Money Laundering, 2022)
Corporate Social Responsibility has been regulated in Law No. 25 of 2007 on investment and Law No. 40 of 2007 on limited liability companies, but in practice it still causes many problems. The first problem is that the regulation does not regulate in detail the implementation of CSR. The second problem is the lack of clarity of the rules and mechanisms for monitoring the implementation of CSR itself. The results of this study indicate that the approach of reflexive legal theory can answer these problems, CSR can be required by the government to every corporation because CSR grows and develops in accordance with the development of business and market reactions, then the rules and mechanisms of supervision by requiring corporations to make reports to the public called social reporting (Social Reporting).